Medial Collateral Ligament Recession for Chronic Medial Knee Laxity - Backes, Jeffrey R.; Wiltfong, Roger E.; Steensen, Robert N. (The Journal of Knee Surgery, 2013)
The medial collateral ligament (MCL) is the primary restraint to valgus stress of the knee. Although the MCL has demonstrated an ability to reliably heal with conservative management, chronic medial instability has been well described following an isolated MCL injury or in combination with an anterior cruciate ligament (ACL) tear. When the MCL heals with persistent medial laxity surgical treatment may be necessary to prevent chronic medial instability and valgus overload of a reconstructed cruciate ligament. We present a simple technique for MCL recession that can be used for isolated MCL laxity as well as in chronic ACL/MCL knee injuries. This technique allows for secure fixation with bone-to-bone healing, avoids donor-site morbidity, maintains relative MCL isometry, and can be performed through a modest incision.
Keywords: chronic; MCL; recession; repair; technique